Determination of Cell Viability, Apoptotic and Necrotic Activities of Boswellia serrata Extract in Liver Cancer (HepG2) and Breast Cancer (MCF7) Cell Lines - Dalkilic, Semih; Dalkilic, Lütfiye Kadioglu; Uygur, Lütfü; Kaya, Ömer (My University, 2024)
Cancer is a very important disease that has existed for a very long time in human history and poses a great threat to humanity today. The scientific world has come up with many innovative treatment approaches, but due to the complexity of cancer cells and their resistance to treatment, a definitive treatment for the fight against cancer has not yet been found. Boswellia serrata has been used for various ailments in many parts of the world from ancient times to the present day, comes from the Burseraceae family, and is commonly known as white gum. B. serrata is a resin tree with very small and few leaves, as it is a plant species that grows as a small tree or shrub 4-6 meters high in the desert. In this study, B. serrata resin was obtained commercially in Gaziantep province and extracted in methanol and hexane solvents. The cytotoxic activity of B. serrata resin extract was determined by MTT Assay (3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide). Apoptotic/necrotic activity was determined by double staining (Hoechst 33342 and propidium iodide). Human breast cancer (MCF7) and human liver cancer (HepG2) cell lines were used in these experiments. As a result of the cell viability assay, hexane 400 ?g/ml extract of B. serrata gave the best effect in HepG2 cell line with 31.63% viable cells, while in MCF7 cell line, B. serrata hexane 800 ?g/ml extract gave the best effect with 13.71% viable cells. When the double staining results were examined, methanol extract applied to the HepG2 cell line caused both necrosis and apoptosis, while cells with disorganized nuclei and membranes were observed in MCF7 cells. When the results of antioxidant activity experiments were analyzed, it was observed that both solvents gave similar results.
Keywords: MTT; HEPG2; Apoptotic; Necrotic; Boswellia serrata; MCF7